The Impact of Participatory Leadership on Teacher Work Motivation at Public Junior High Schools in Pemalang District, Pemalang Regency - Gudiyatmi .; Endang Wuryandini; Noor Miyono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
Teachers would work professionally when they have high work motivation because it is such a mental boost that comes from inside and outside of themselves which help to carry out the task of achieving the goals / objectives that have been set with full of awareness and responsibility. The aims of this study are to determine the effect of: participatory leadership, toward teachers’ work motivation partially and simultaneously. This study used quantitative approach. Among 287 populations of public junior high school teachers in Pemalang district, 167 respondents were chosen using the proportional random sampling technique. The data analysis used in this study is descriptive analysis, classic assumption test and regression test using SPSS version 17 for Windows. The results shows that (1) simple regression test for variable X on Y obtained the correlation value (r) = 0.915, meaning that the correlation was incredibly strong, with Adjusted R2 = 0.837, meaning that the influence of participatory leadership on teachers’ work motivation is 83.7% and remaining at 16,3% accounting teacher performance is determined by factors other than research.Keywords: Participatory Leadership, Teachers’ Work Motivation